Pimping fictions : African American crime literature and the untold story of Black pulp publishing - Gifford, Justin, 1975- (UPCC book collections on Project MUSE. Literature., 2013)
"Lush sex and stark violence colored Black and served up raw by a great Negro writer, " promised the cover of Run Man Run, Chester Himes' pioneering novel in the black crime fiction tradition. In this book, the author provides a hard-boiled investigation of hundreds of pulpy paperbacks written by Himes, Donald Goines, and Iceberg Slim (aka Robert Beck), among many others. The author draws from an impressive array of archival materials to provide a literary and cultural history of this distinctive genre.